Efficiency Unleashed: Streamlining Operations for Organizational Excellence - Brastoro; Nargis, Lusia (Ambidextrous Journal of Innovation Efficiency and Technology in Organization, 2024)
This study explores the interplay between operational efficiency, innovation practices, and employee engagement in driving organizational excellence at PT Bandung Indah Gemilang. Using a quantitative research design and random sampling of 70 employees, the study analyzes direct and indirect effects using Smart PLS. Results indicate that operational efficiency and innovation practices both have significant positive impacts on organizational excellence. Additionally, employee engagement significantly mediates these relationships, enhancing the overall effect of operational efficiency and innovation practices on organizational excellence. The findings emphasize the critical role of employee engagement in maximizing the benefits of operational efficiency and innovation, providing actionable insights for organizations aiming to achieve and sustain high performance.